The WRKY10‐VQ8 module safely and effectively regulates rice thermotolerance. (1st May 2022) - Chen, Sique; Cao, Hongrui; Huang, Baolin; Zheng, Xiujuan; Liang, Kangjing; Wang, Guo‐Liang; Sun, Xinli
Abstract: WRKY transcription factors (TFs) play crucial roles in biotic and abiotic stress responses. However, their roles in thermal response are still largely elusive, especially in rice. In this study, we revealed the functions of WRKY10 TF and VQ8 protein containing VQ motif in rice thermotolerance. Overexpression of WRKY10 or loss of VQ8 function increases thermosensitivity, whereas conversely, overexpression of VQ8 or loss of WRKY10 function enhances thermotolerance. Overexpression of WRKY10 accelerates reactive oxygen species (ROS) accumulation in chloroplasts and apoplasts, and it also induces the expression of heat shock TF and protein genes. We also found that WRKY10 regulates nuclear DNA fragmentation and hypersensitive response by modulating NAC4 TF expression. The balance between destructive and protective responses in WRKY10 ‐overexpression plant is more fragile and more easily broken by heat stress compared with wild type. In vitro and in vivo assays revealed that VQ8 interacts with WRKY10 and inhibits the transcription activity via repressing its DNA‐binding activity. Our study demonstrates that WRKY10 negatively regulates thermotolerance by modulating the ROS balance and the hypersensitive response and that VQ8 functions antagonistically to positively regulate thermotolerance. The functional module of WRKY10‐VQ8 provides safe and effective regulatory mechanisms in the heat stress response. Summary statement: The role of WRKY transcription factors in thermal response is largely elusive, especially in rice. Our results showed that WRKY10 and its interacting partner VQ8 played an antagonistic role, safely and effectively regulating rice thermotolerance by modulating reactive oxygen species (ROS) balance and hypersensitive response.